Multistep Approach Points to Compounds Responsible for the Biological Activity and Safety of Hydrolates from Nine Lamiaceae Medicinal Plants on Human Skin Fibroblasts - Katarina Smiljanić; Ivana Prodić; Sara Trifunovic; Maja Krstić Ristivojević; Milica Aćimović; Jovana Stanković Jeremić; Biljana Lončar; Vele Tešević (Antioxidants, 2023)
As byproducts of essential oil distillation, hydrolates are used in natural cosmetics/biomedicine due to their beneficial skin effects. However, data on their safety with relevant biological targets, such as human skin cells, are scarce. Therefore, we have tested nine hydrolates from the Lamiaceae family with skin fibroblasts that are responsible for extracellular collagenous matrix builds. Thyme, oregano, and winter savoury hydrolates showed several times higher total phenolics, which correlated strongly with their radical scavenging and antioxidative capacity; there was no correlation between their viability profiles and the reducing sugar levels. No proteins/peptides were detected. All hydrolates appeared safe for prolonged skin exposure except for 10-fold diluted lavender, which showed cytotoxicity (~20%), as well as rosemary and lavandin (~10%) using viability, DNA synthesis, and cell count testing. Clary sage, oregano, lemon balm, and thyme hydrolates (10-fold diluted) increased fibroblast viability and/or proliferation by 10–30% compared with the control, while their viability remained unaffected by Mentha and winter savoury. In line with the STITCH database, increased viability could be attributed to thymol presence in oregano and thyme hydrolates in lemon balm, which is most likely attributable to neral and geranial. The proliferative effect of clary sage could be supported by alpha-terpineol, not linalool. The major volatile organic compounds (VOCs) associated with cytotoxic effects on fibroblasts were borneol, 1,8-cineole, and terpinene-4-ol. Further research with pure compounds is warranted to confirm the roles of VOCs in the observed effects that are relevant to cosmetic and wound healing aspects.